Aspek Yuridis Kejahatan Phishing dalam Ketentuan Hukum di Indonesia - Yazid Haikal Lokapala; Fuad Januar Nurfauzi; Yeni Wdowaty (Universitas Muhammadiyah Yogyakarta, 2024)
Phishing is a form of cybercrime that is committed by tricking victims into providing personal or confidential information via email, websites or fake social media. Phishing crimes can cause material and immaterial losses for victims, such as identity theft, misuse of credit cards, or defamation. Therefore, it is necessary to have legal efforts to eradicate phishing crimes and protect the rights of victims. This paper aims to examine the criminal acts of phishing crimes in the world of cybercrime in terms of Indonesian juridical aspects. The research method used is a normative legal research method with a statutory approach and a case approach. The data used is secondary data in the form of primary, secondary and tertiary legal materials. The data analysis technique used is a qualitative analysis technique. The results of the research show that the crime of phishing in the world of cybercrime can be categorized as a crime of fraud as regulated in Article 378 of the Criminal Code or an act of embezzlement as regulated in Article 372 of the Criminal Code. In addition, phishing crimes can also be subject to sanctions based on Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), specifically Article 28 paragraph (1) and Article 45 paragraph (1) of the ITE Law. However, in practice, there are still obstacles in law enforcement against phishing crimes, such as difficulties in identifying perpetrators, lack of coordination between law enforcement, and low public awareness to report phishing cases. Therefore, preventive and repressive efforts are needed to overcome this problem, such as increasing people's digital literacy, conducting socialization and education about the dangers of phishing, and strengthening cooperation between related parties in law enforcement.